Journal of Contradicting Results in Science - Cock, I.E. (Pharmacognosy Communications)
There is currently a bias to publish only results that are perceived as ‘successful’; i.e. results that are positive (showing a significant finding) and/or that fit within the current model for a given research field. Results that are negative (supporting the null hypothesis) or are inconclusive are often not published, leading to a biased (perhaps false) representation in the published literature. Furthermore, results that refute a current paradigm often meet with considerable resistance to publication. The Journal of Contradicting Results in Science (JCRSCI) (http://www. jcrsci.org/) has been established by SciBiolMed.Org (http://www.scibiolmed.org) to address this imbalance. JCRSCI encourages the submission of original research articles resulting in controversial/negative results. By counterbalancing the selective reporting of ‘positive’ results, JCRSCI aims to foster discussion of controversial, unexpected and negative results and their context within current paradigms.